BENEFITS OF MAIZE FARMING (Zea mays L) IN AT BANGKAL'S SUB-DISTRICT DISTRICT CEMPAKA BANJARBARU'S CITY SOUTH KALIMANTAN PROVINCE - Bahrun Bahrun (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2019)
This study aims to know technically corn farming, know economically about the costs, revenues and profits of corn farming in Bangkal VillageThe number of farmers who tried corn farming for F1 Bisi-2 superior varieties was 60 people, then Simple Random Sampling was 35% (21 people) of the entire population.Corn farming activities in Bangkal Village with an cultivated land area of an average of 0.81 hectares / farmer. The total cost incurred for corn farming in one production process is 5,028,858.48 / farmer or Rp. 6,208,467.25 / ha. The production obtained is 54,827.05 kg / farmer or an average of 5,959.32 kg / ha (5.96 tons / ha), with prices prevailing at that time, namely Rp.4,000 / kg. Average revenue of Rp. 19.308,190.48 / farmer / planting season or an average of Rp. 23,837,272.19 / ha. Average profit of Rp. 14,279,332.00 / farmer or an average of Rp. 17,628,804.94 / ha